Diseño estructural de acero del techo parabolico para el coliseo polideportivo Acudesi - Trujillo - Lozano Oliva, Cesar Aurelio (2019)
The present work entitled "Steel Structural Design of the Parabolic Roof for the Acudesi Sports Coliseum - Trujillo", presents the structural analysis and costs of the members that build the parabolic roof, based on the load and resistance method (LRFD). The structure to be designed has the following dimensions: 25 m of light, 32 m long and 5 m of arrow making a flat area of 800 m2. Furthermore, an approximate weight of 23198 kg was calculated. The Peruvian rules of the National Building Regulations (RNE) were applied, as well as international standards such as AISI, AISC, AWS and ASCE. Also, the analysis and simulation of the structure are supported by Solidworks and SAP2000 softwares. The structure is made of ASTM A-36 steel. The design was made with 05 main beams (arches) designed as Warren armatures with smooth round bars with diameters of 1 ½ inches (main strings), 5/8 inches (diagonal or lattice) and ½ inches (connections); 76 joists (belts) designed as Warren armatures with U-channel chords of 2 "x2.58 lbs / ft (top rope), smooth round bar ½ inches of diameter (lower chord) and smooth round bar diagonals of 5/8 inches of diameter. It has 10 columns of H section (H24x9x76 LBS), being the coverage of plate TR-4 CURVED Zincalum steel ASTMA792 with thickness of 0.45mm. The cost analysis of the parabolic roof resulted in a total cost of S/. 150,402.14. The blueprints are presented in AutoCad.